The effect of perirenal fat stranding on infectious complications after ureterorenoscopy in patients with ureteral calculi - Erhan Demirelli; Ercan Öğreden; Cemil Bayraktar; Alptekin Tosun; Ural Oğuz (Asian Journal of Urology)
Objective: Perirenal fat stranding (PFS) is linear areas of soft-tissue attenuation in the perirenal space on non-contrast computed tomography. The present study aimed to investigate whether PFS is associated with infectious complications after ureterorenoscopy (URS) in patients with ureteral calculi in any location. Methods: The data of 602 patients with ureteral stones who underwent URS were analyzed retrospectively. The patients were divided into two groups as Group 1 (PFS not detected) and Group 2 (PFS detected). Gender, and age of patients, size, side, and location of the stone, operation time, double-J stent insertion status, perioperative ureter injury, postoperative infection after URS and related complications, and duration of hospital stay were compared. Results: While PFS was not detected in 530 patients, PFS was detected in 72 patients. The mean age, male/female ratio, side and localization of the stones, operation time, and perioperative insertion of the double-J after lithotripsy were statistically similar (p>0.05). The median stone diameter was smaller in Group 2 (9 mm vs. 8 mm) (p=0.033). Fever was observed in 30 and 38 patients in Group 1 and Group 2, respectively (p=0.0001). Urinary tract infection was detected in 24 and 27 patients in Group 1 and Group 2, respectively (p=0.0001). The urosepsis did not occur in any patients in Group 1, whereas 8 (11.1%) patients in Group 2 experienced urosepsis (p=0.0001). Conclusion: According to the results of the present study, patients with ureteral stones accompanied by PFS are much more prone to ureteral injuries and infectious complications such as urinary tract infection, fever, and sepsis after URS.